ECUADENDRO 2025: THE 1ST ECUADORIAN DENDROCHRONOLOGY CONFERENCE - PEÑA, KELLY; Kirchhefer, Andreas J.; Edvardsson, Johannes; Pederson, Neil; Islam, Mahmuda; Bhattacharjee, Kanta; Kabir, Chowdhury Rafatul; Shah, Santosh K.; Rahman, Tanveer W.; Stahle, David W.; Groenendijk, Peter; Khan, Adam; et al. (Tree-Ring Research, 2025)
The 1st Ecuadorian Dendrochronology Conference (ECUADENDRO 2025) took place in Daule, Ecuador, on January 23–24, 2025, with the generous sponsorship of the Tree-Ring Society. The event attracted 230 participants from 45 countries, bringing together leading experts in various subfields of tree-ring science, including dendroclimatology, dendroecology, dendrogeomorphology, dendroarchaeology, and cellular dendrochronology. Fifteen international speakers presented a diverse range of case studies from countries such as Ecuador, Norway, Sweden, India, Bangladesh, the United States, Brazil, Argentina, Pakistan, and Germany. Their contributions highlighted significant advancements in tree-ring research and the global progress in the field. The conference discussions emphasized emerging trends and future directions for tree-ring science, shedding light on new areas for continued research and collaboration.
CRIS-Team Scopus Importer:2026-01-26
Keywords: dendroarchaeology; dendrochronology; dendroclimatology; dendrogeomorphology; Ecuadendro; tree rings